Analysis of a case report of meningitis caused by Listeria monocytogenes - Chen, Lihui; Pei, Manman; Wang, Xingxing; Zhang, Yongfeng; Ma, Yuquan; Chen, Yifei; Ahmad, Ishtiaq (Frontiers in Medicine, 2024)
Listeria monocytogenes is a Gram-positive bacterium transmitted to humans through contaminated food, water, and animal faeces, posing a public health risk. Listeria monocytogenes is difficult to isolate and is not sensitive to first-line treatment with broad-spectrum cephalosporins for bacterial meningitis. Listeria meningitis is rare but can progress rapidly and may be accompanied by serious complications (hydrocephalus, ventricular inflammation, cerebral palsy, and brain abscess) and a high mortality rate.'s a retrospective analysis of the clinical characteristics and treatment of a rare case of Listeria monocytogenes infection. Using laboratory indicators such as white blood cells (WBC), C-reactive protein (CRP), and procalcitonin (PCT), three detection methods (cerebrospinal fluid/blood culture, Targeted gene sequencing technology (tNGS), and Metagenomic next-generation sequencing technology (mNGS) combined with clinical manifestations of patients, analyze the use plan and prognosis of antibiotics in patients. The patient in this case initially had neurological symptoms such as fever, headache, unclear consciousness, and vomiting; laboratory indicators include elevated WBC, CRP, and PCT. Listeria monocytogenes was cultured in both the patient's cerebrospinal fluid and blood 2 samples. After treatment with penicillin and meropenem, the patient recovered and was discharged without any sequelae.Due to the rarity of Listeria monocytogenes, there may be deficiencies and difficulties in clinical differential diagnosis, making it difficult to achieve targeted antibiotic treatment. Therefore, accurate identification of Listeria monocytogenes and relevant laboratory inflammation indicator testing, combined with traditional culture methods and NGS testing, through empirical coverage of Listeria monocytogenes, targeted antibiotic treatment ultimately impacts clinical outcomes significantly.